Reorientation of Rural Development as a Base for Improving Land Ownership Distribution at Farmer Level - Jamal, Erizal (+622518321746, 2013)
The problem of unbalanced land distribution at farm level in Indonesia has hampered many efforts to improve rural livelihoods. Several development programs that have been implemented by the government have not been fully benefitted by smallholders due to various reasons, and in many cases this condition even further widen inequality, because only landowners who are able to take advantage the vast range of opportunities created through the programs. In the future, a reorientation of rural development is needed with more emphasis on improving farmers? access to information, capital, technology, and their capacity to take advantage of opportunities that are locally available. Reorientation of rural development will be initiated with changes of the approaches in the planning and implementation of development, with emphasis on the development of diverse types of businesses, as well as capacity building of the community to take advantage of the growing local opportunities. These efforts need to be supported by the implementation of rural development with an integrated approach, through a strong cooperation at the district level under the coordination of District Development Planning Agency. Rural development planning should be directed to two main issues. Firstly, open up new business opportunities, especially those non-based land activities. Secondly, build the community capacity to capture the existing business opportunities. The technologies being developed should be neutral with respect to farmers land ownership, and the technology dissemination is supposed to be proportional in order to reach all levels of farmers.